Friction stir welding of dissimilar metal - Sahidi, Sujanuriah (2013)
Friction Stir Welding is a solid – state thermo – mechanical joining process (a combination of extruding and forging). Joining of steels to aluminium alloys can be used for producing steel/aluminium bimetallic parts in a wide range of industrial areas. The overall aim of this study is to get the optimum parameters for the materials under considerations, to investigate the Heated Affected Zone (HAZ), Thermo – Mechanical Affected Zone (TMAZ) and Weld Nugget (WN) besides to study the defects occurring during welding process by applying different parameters chosen. The welding process was done by using conventional milling machine. Three experiments being used are the Tensile Testing, Optical Microscopy (OM) and Electron Scanning Microscopy (SEM) to get the strength of the joint and the metallographic studies. The findings also found out that suitable parameters being choose give less defect and intermetallic compounds (IMCs). Therefore, at higher speed and lower tool plunge length, the joint strength decreased due to lack of bonding between aluminium and steel.